Análisis de factores que contribuyeron y/o limitaron la implementación de la estrategia “Aprendo en Casa” en las Instituciones Educativas del nivel secundario rurales y urbanas del distrito de Paramonga, provincia de Barranca, Región Lima Provincias, en el marco de la pandemia por la COVID-19, en los años 2020 y 2021 - Oscco Aroni, Luz Nélida (2024)
This research is aimed to determine the limiting and contributing factors regarding the implementation of AeC - AeC (Home school) strategy in two ruraland-urban-area schools from Paramonga district, Barranca province, Lima Provincias region during the COVID-19 pandemic, 2020 -2021. Using the mixed research method, directors and teachers were interviewed, focus groups were organized with students and parents, a student's life history and a student survey were conducted; with the objective of knowing how the development and participation in the pedagogical activities was, how the access and use of the technological, financial and human resources of the strategy was, the leadership style of the managers and the perception of the actors involved. Some findings were found like limiting factors, the lack of access of internet and connectivity to implement efficiently the AeC Casa strategy. Also, the limited access to educational platform channels of AeC strategy. On another hand, some contributing factors were the collaborative work of principals and teachers in the school activities adaptation and the supply of tablets by the Ministry of Education (MINEDU, in Spanish). Therefore, as a result of the results of this research, an improvement proposal is presented to improve the implementation of the I Learn at Home strategy or distance education, since although its implementation began during the years 2020 and 2021 Due to the COVID-19 pandemic, today it is the teaching modality that is here to stay and the one that the Ministry of Education recommends using whenever there are adverse circumstances that do not allow in-person education.